Polyetylenová choroba - Sosna, A; Radonský, T; Pokorný, D; Veigl, D; Horák, Z; Jahoda, D (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2003)
PURPOSE OF THE STUDY: The experience obtained during revision surgery and findings of polyethylene granulomas in surrounding tissues of replacement as well as marked differences in the viability of implants resulted in the study of polyethylene disease and its basic mechanisms producing the development of osteoaggressive granulomas. We investigated the morphology of particles and their number in tissues surrounding the implant. The aim of our study was to develop a method for the detection of polyethylene particles in tissues, to identify different types of wear and to assess factors that may influence the viability of joint arthroplasty in general. MATERIAL: Every revizion of joint arthroplasty performed during the last five years was evaluated in terms of the presence of polyethylene granules and the viability state of articular polyethylene inserts. A total of 55 samples were taken from tissues around loosened endoprostheses. The location of each sample was exactly determined. METHOD: A technique was developed to identify wear particles and to visualize them after all organic structures of a polyethylene granuloma were dissolved with nitrogenic acid. RESULTS: The viability of articular polyethylene implants showed extreme differences in relation to different periods of manufacture and probably also to different methods of sterilization. Articular inserts sterilized with formaldehyde (the method used at the beginning of arthroplasty in our country) showed the highest viability and the lowest wear. The polyethylene particles present in tissues surrounding the implant were characterized in terms of morphology and size. DISCUSSION: The comparison of literature data and our results has revealed that there are many unknown facts about the quality and structure of polyethylene. The method of sterilization also appears to play a role. Because the issue is complex, we were not able to identify all factors leading, in some cases, to an early and unexpected failure of the implant and we consider further investigation to be necessary. CONCLUSIONS: Polyethylene disease is an important factor limiting the viability of joint arthroplasty. It results from a complex interaction of polyethylene particles arising by wear with surrounding tissues. The particles, less than 0.5 micron in size, are phagocytized by macrophages and, by complex mechanism of expression of inflammation mediators, they result in the inhibition of osteogenesis and activation of osteoclastic processes. The previous methods of sterilization with formaldehyde vapors apparently reduced wear influenced the resistance of polyethylene to wear to a lesser degree. A method was developed to detect these particles and to characterize their morphology in the tissues of a polyethylene granuloma.
Keywords: Polyethylenes; Foreign-Body Reaction; Prosthesis Failure; polyethylen; Joint Prosthesis; Polyethylene; lidé; selhání protézy; Particle Size; protézy kloubů; Humans; polyethyleny; velikost částic; reakce na cizí těleso